2003
DOI: 10.1046/j.1472-8206.2003.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal effects of nonsteroidal anti‐inflammatory drugs

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) causes extensive damage to the gastrointestinal (GI) tract. The underlying mechanisms of gastric injury include topical irritant actions that disrupt the epithelial barrier, as well as the inhibition of cyclo-oxygenase (COX), which is predominantly the COX-1 isoform in the mucosa. This damage can be attenuated by antisecretory agents or by mucosal protective agents such as the synthetic prostanoids or nitric oxide (NO) donors. Compounds designed to attenuate topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 94 publications
6
86
0
3
Order By: Relevance
“…Adverse GI effects of NSAIDs including GI ulceration [1][2][3][4] result in 100,000 emergency admissions, high medical costs and 17,500 deaths per year in the US alone [5,6]. Despite extensive investigation, the mechanisms responsible for NSAID-associated GI damage are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse GI effects of NSAIDs including GI ulceration [1][2][3][4] result in 100,000 emergency admissions, high medical costs and 17,500 deaths per year in the US alone [5,6]. Despite extensive investigation, the mechanisms responsible for NSAID-associated GI damage are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…COXs are critical for the maintenance of the intestinal epithelium (7). COX inhibitors damage the gastrointestinal tract, which can be alleviated by synthetic prostanoids (8). Inflammatory bowel disease is associated with high levels of COX (9 -11).…”
mentioning
confidence: 99%
“…Earlier studies have reported that NSAIDs, promote ischemic and inflammatory alterations, which result in gastric neutrophil infiltration, and increase in oxidative stress (31,34) . Further, the H 2 receptor blocker Ranitidine has been observed to reduce ischemia/reperfusion-induced liver injury by inhibiting neutrophil activation directly, or indirectly by inhibiting the production of TNF-α, which is a potent activator of neutrophils (22) .…”
Section: • Change In Phmentioning
confidence: 99%